2015
DOI: 10.1021/acs.jpcb.5b00808
|View full text |Cite
|
Sign up to set email alerts
|

Photoactive Fluoropolymer Surfaces That Release Sensitizer Drug Molecules

Abstract: We describe a physical-organic study of two fluoropolymers bearing a photoreleasable PEGylated photosensitizer which generates 1O2(1Δg) [chlorin e6 methoxy tri(ethylene glycol) triester]. The surfaces are Teflon/polyvinylalcohol (PVA) nanocomposite and fluorinated silica. The relative efficiency of these surfaces to photorelease the PEGylated sensitizer [shown previously to be phototoxic to ovarian cancer cells (Kimani, S. et al J. Org. Chem 2012, 77, 10638)] was slightly higher for the nanocomposite. In the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 88 publications
0
20
0
2
Order By: Relevance
“…(iii) Figure shows the silica tip with CF 3 CF 2 CF 2 CF 2 groups where facile sensitizer release is expected. For example, PEGylated sensitizer molecules would otherwise adhere to non‐fluorinated silica . Thus, the fluorinated device tip yields repellent characteristics to discharge the sensitizer and also yields high oxygen concentrations consequently producing highly focused quantities of singlet oxygen.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…(iii) Figure shows the silica tip with CF 3 CF 2 CF 2 CF 2 groups where facile sensitizer release is expected. For example, PEGylated sensitizer molecules would otherwise adhere to non‐fluorinated silica . Thus, the fluorinated device tip yields repellent characteristics to discharge the sensitizer and also yields high oxygen concentrations consequently producing highly focused quantities of singlet oxygen.…”
Section: Resultsmentioning
confidence: 99%
“…We and others have observed that polyethylene glycol (PEG) groups bonded to chlorophyll sensitizers can increase their solubility in solution, cell uptake, and phototoxicity in cancer cells. But previous work with chlorin e 6 had required chemically bonding each PEG group individually, with the third PEG adding in low yield (triPEG‐chlorin silica 2 and triPEG‐chlorin Teflon/PVA nanocomposite 3 , Figure ). This led us to pose the question: Can three PEG groups be installed in one step by the use of a galloyl group at its connecting point in tip fabrication ( 1 , Figure )?…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We hypothesized that the U shape of the bridge would increase the exposure of the ethene site for enhanced 1 O 2 ‐based sensitizer release. We expected this system to be an improvement over our previous succinate and dimethylene‐linked sensitizer photorelease systems. In this system, the 1 O 2 , which triggers the sensitizer release, is generated by the sensitizer surface.…”
Section: Introductionmentioning
confidence: 99%